EFEKTIVITAS SERTIFIKAT ELEKTRONIK SEBAGAI BUKTI KEPEMILIKAN HAK ATAS TANAH DALAM RANGKA MEWUJUDKAN E-GOVERNMENT - Eka Ermala; Arga Chon Feriandref, Othman Ballan, Mubaraq, Duwi Aryadi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This research aims to identify and analyze the effectiveness of electronic certificates as proof of ownership of land rights and how electronic land certificates are able to realize the implementation of electronic-based government (E-government), the advantages and disadvantages of conventional certificates and electronic certificates, and discuss the inhibiting factors for the implementation of electronic certificates in efforts to realize E-government. This study uses a normative juridical research method, by reviewing laws and regulations, including Law Number 1 of 2024, the second amendment to Law Number 11 of 2008 concerning ITE, Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (E- government), Regulation of the Ministry of ATR / BPN Number 3 of 2023 concerning the Issuance of electronic documents in land registration activities, Government Regulation of the Republic of Indonesia Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, Government Regulation Number 24 of 1997 concerning Land Registration.